A REVIEW OF EXPERIMENTAL STUDY AND CFD BASED SIMULATION OF CLOSED LOOP PULSATING HEAT PIPE - Tiwari, Monika; Diwakar, Nilesh (International Journal of Research -GRANTHAALAYAH, 2016)
Closed loop pulsating heat pipe is very effective tool for removal of heat from very small electronic devices. In this study various literature related to CLPHP are studied and various parameters that effect the performance of CLPHP. It was found from literature that length of pipe, Number of turns, cooling fluid effect the performance of pipe.